Remote sensing for evaluating crop water stress at field scale using infrared thermography: potential and limitations - Taghvaeian, Saleh, author; Chávez, José L., author; Altenhofen, Jon, author; Trout, Tom, author; DeJonge, Kendall, author; Colorado State University, publisher (Colorado State University. Libraries, 2013)
Over the past few decades, the competition for freshwater resources has substantially increased in arid/semi-arid areas, exacerbating the pressure on the largest user of water, namely agriculture, to consume less water. However, reducing crop consumptive water use or evapotranspiration through water stress can have a negative impact on production economics if not precisely managed. Remote sensing of crop canopy temperature is a scientifically-based and easy-to-apply method that can be used at field scales to evaluate crop water status at or near real-time. In this study, thermal images of maize canopy under two deficit irrigation regimes were acquired using a hand-held thermal camera. The results showed that the low-frequency deficit irrigation treatment resulted in higher maize temperatures compared to the high-frequency deficit irrigation regime. A methodology for converting the temperature value of each pixel into a spatially variable crop water stress index (CWSI) is described. Within the low-frequency deficit irrigation treatment, estimated CWSI values were correlated with spatial variations in soil texture. Finally, the potential of infrared thermography and current limitations are discussed in detail.
Hydrology days 2013
AGU hydrology days 2013
2013 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2013.